1994
DOI: 10.1016/0896-8446(94)90050-7
|View full text |Cite
|
Sign up to set email alerts
|

Methane to methanol in supercritical water

Abstract: We examined the feasibility of producing methanol from the partial oxidation of methane in nearcritical and supercritical water. Oxygen was always the limiting reactant. The parameter space investigated experimentally included temperatures between 349 and 481 "C, batch holding times between 1 and 9 min, water densities between 0.15 and 0.35 g mL-I, initial methane to water molar ratios between 0.05 and 0.27, and initial methane to oxygen molar ratios between 10 and 26. Experiments within this parameter space l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…While the dearth of experimental studies under similar physical and chemical conditions precludes direct comparison, compounds of both organic classes do exist as products of organic reactions with supercritical water in elevated temperature and pressure environments (Savage et al, 1994). Formation of alcohols and carboxylic acids has been confirmed unambiguously in this study by repetitive experiments and high-resolution mass spectrometry.…”
Section: Alcohols and Carboxylic Acidsmentioning
confidence: 83%
“…While the dearth of experimental studies under similar physical and chemical conditions precludes direct comparison, compounds of both organic classes do exist as products of organic reactions with supercritical water in elevated temperature and pressure environments (Savage et al, 1994). Formation of alcohols and carboxylic acids has been confirmed unambiguously in this study by repetitive experiments and high-resolution mass spectrometry.…”
Section: Alcohols and Carboxylic Acidsmentioning
confidence: 83%
“…The authors also reported a reaction network and pseudo-first-order rate constants that were consistent with their experimental data. Savage et al (1994b) also reported experimental results for the conversion of methane to methanol near the critical point of water. Unlike Dixon and Abraham, this group did not use a catalyst.…”
Section: Partial Oxidation Of Alkylaromatics and Ofefksmentioning
confidence: 93%
“…[7,12], are often limited to pressures below 20 bar, whereas studies of homogeneous partial oxidation of CH 4 to CH 3 OH [43][44][45][46][47][48][49][50][51][52] typically operate in the 20-100 bar and 600-900 K range, similar to the present study but limited to very reducing conditions. Finally, data are available on oxidation of CH 4 in supercritical water (663-923 K, 35-350 bar) [53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%